Analysis of the Role of Emotional Intelligence on Religious Moderation Attitudes in Buddhist College Students: A Quantitative Descriptive Study - Chintya Astana, Astri; Permatasari, Tisya; Susijati, Susijati; Rahma, Muninggar (Devotion : Journal of Research and Community Service, 2025)
Emotional intelligence is an important factor in shaping individual attitudes and behaviors, including in the context of religious moderation. This study aims to analyze the relationship between the internalization of religious moderation values and the emotional intelligence of students in Buddhist Colleges in Indonesia. The values of religious moderation are measured through indicators of national commitment, tolerance, anti-violence, and acceptance of traditions. Meanwhile, emotional intelligence includes self-awareness, self-regulation, motivation, empathy, and social skills. The research employed a quantitative approach with a correlational design. Data were collected using questionnaires distributed to students and analyzed using statistical correlation tests. The results of the study indicate a significant relationship between the internalization of religious moderation values and the level of students' emotional intelligence. Students with a high internalization of religious moderation values tend to exhibit better emotional intelligence, particularly in the aspects of empathy and self-regulation. These findings highlight the importance of integrating religious moderation values into higher education curricula to support the emotional and character development of students.